General criminalistics : teaching manual - Bonane, Sylvanus Mushi (London : Sciencia Scripts, 2025)
"This manual contains the teachings of criminalistics, which is the set of sciences and techniques used in justice to establish the materiality of the criminal act and the guilt of the person who committed it. Unlike criminology, which studies the causes and manifestations of the criminal phenomenon, forensic science studies the criminal investigation and trial. Its field of work extends from the scene of the crime to the testimony given in court, and includes a range of specialized laboratory analyses, focusing on the crime, the criminal and the victim. Based on the premise that the criminal always leaves traces at the scene of the crime, and that when he leaves the scene of the crime, he also brings other traces on his person (body, clothing, objects, used items), it is highly advisable that criminal investigation, the highlight of which is often marked by the examination of the crime scene, the processing of clues and traces, and the appropriate interrogation of suspects."
Includes bibliographical references and index/Rujukan : mukasurat
Keywords: Criminal investigation; Forensic sciences